The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/nu9030220
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Knowledge of Nuts amongst Health Professionals in New Zealand

Abstract: Despite their nutritional value, population-level nut consumption remains low. Studies suggest that individuals would eat more nuts on their doctor’s advice, making health professionals potentially important for promoting nut consumption. This cross-sectional study aimed to examine the perceptions and knowledge of nuts and the predictors of nut promotion among health professionals in New Zealand. Dietitians, general practitioners (GPs), and practice nurses were identified from the Electoral Roll and invited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…A recent survey which examined barriers to and facilitators of nut consumption among the general public in New Zealand found that dental issues was the most frequently reported reason for the avoidance of nut consumption [ 91 ]. In addition, in a survey among health professionals (dietitians, general practitioners, practice nurses), dental issues were reported by around 14% of participants as a reason why they advise some of their patients to eat fewer nuts [ 92 ]. Furthermore, among dietitians, dental issues were one of the top five reasons why they advised their patients to eat fewer nuts.…”
Section: Overcoming Potential Barriers and Side-effects Of Nutsmentioning
confidence: 99%
“…A recent survey which examined barriers to and facilitators of nut consumption among the general public in New Zealand found that dental issues was the most frequently reported reason for the avoidance of nut consumption [ 91 ]. In addition, in a survey among health professionals (dietitians, general practitioners, practice nurses), dental issues were reported by around 14% of participants as a reason why they advise some of their patients to eat fewer nuts [ 92 ]. Furthermore, among dietitians, dental issues were one of the top five reasons why they advised their patients to eat fewer nuts.…”
Section: Overcoming Potential Barriers and Side-effects Of Nutsmentioning
confidence: 99%
“…Even though nuts contain very high amounts of fat, their consumption has repeatedly been shown not to be associated with weight gain [ 11 , 17 , 18 , 19 ], but instead with moderate weight loss or weight stability, as reported in a large prospective study, involving 373,000 participants from 10 European countries [ 11 ]. Despite these findings, there is still a common belief that nut intake is associated with weight gain risk, even among health care professionals [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study methods are described in detail elsewhere ( Brown et al, 2017 ; Yong et al, 2017 ), and only essential details are presented here.…”
Section: Methodsmentioning
confidence: 99%